Germany's Federal Climate Change Act. (20th October 2021) - Flachsland, Christian; Levi, Sebastian
ABSTRACT: Despite significant renewable energy expansion in the past, Germany has encountered difficulties in meeting its national greenhouse gas emission targets. In response, Germany adopted the Federal Climate Change Act (CCA) in 2019. We analyze the state of climate governance in Germany before the CCA, the main design elements of the CCA, and assess the potential of the CCA to change German climate governance. Drawing on policy integration theory and 26 semi-structured interviews with senior policymakers and stakeholders, we find that German climate governance before the CCA was only moderately integrated. The sectoral emission targets legislated by the CCA make climate change mitigation a priority sector goal in non-energy sectors, and CCA provisions for monitoring, assessing and implementing policy reforms promise to enhance alignment of instruments with targets over time. Overall, the CCA advances a multi- rather than cross-sector climate governance, failing to advance coordination across sectors and ministries.